Strategies to Improve the Quality of Education - M.Said, Ilham; Farizi Rambe, Muarif Al; Bagus Setiawan, Heri Cahyo (Universitas Muhammadiyah Gresik, 2024)
Schools as a leading institution in carrying out the development of the quality of education must be able to provide the right capacity in creating good graduates, for that we need an appropriate management model so that schools can carry out their functions properly. Efforts to improve to achieve quality education are not only fulfilling the input and output aspects, but more importantly the process aspect, which means decision making, program management, institutional management process, teaching and learning process and monitoring and evaluation process with a note that the process teaching and learning has the highest level of importance compared to other processes. And also must have a strategy to improve the quality of education in any way so that education is more creative and innovative.